Servant leadership for higher education : principles and practices - Wheeler, Daniel W., 1939- (San Francisco, Calif. : Jossey-Bass, 2012)
'If higher education is to fulfill its mission, the academy must continue to emphasize the ideals of thought, reflection, and development as well as action. This book stresses the importance of understanding that service is a pre-requisite to leadership. This practical book contains leadership principles and strategies and is based on research and best practice. The book is organized around ten principles of servant leadership and how these principles apply to common issues faced in departments and institutions of higher education. The situations addressed are representative so that it is easy to see how the principles apply to other concerns or issues'--
Includes bibliographical references (p. 173-176) and index.
Keywords: Universities and colleges -- Administration; Educational leadership; Servant leadership